Quantitative proteomics reveals that miR‐222 inhibits erythroid differentiation by targeting BLVRA and CRKL. (24th January 2018) - Jiang, Li; Wang, Xing; Wang, Yong; Chen, Xiaoyan
Abstract : miR‐222 plays an important role in erythroid differentiation, but the potential targets of miR‐222 in the regulation of erythroid differentiation remain to be determined. The target genes of miR‐222 were identified by proteomics combined with bioinformatics analysis in this study. Thirteen proteins were upregulated, and 13 were downregulated in K562 cells following transfection with miR‐222 inhibitor for 24 and 48 hours. Among these proteins, BLVRA and CRKL were upregulated after transfection of miR‐222 inhibitor in K562 cells and human CD34+ HPCs. Moreover, miR‐222 mimics reduced and miR‐222 inhibitor enhanced the mRNA and protein levels of both BLVRA and CRKL. Luciferase assay showed that miR‐222 directly targeted 3′‐UTR of BLVRA and CRKL. In addition, overexpression of either BLVRA or CRKL or both increased the erythroid differentiation of K562 cells, while silencing of either BLVRA or CRKL or both by siRNA significantly attenuated hemin‐induced erythroid differentiation of K562 cells. Our results indicated that BLVRA and CRKL are targets of miR‐222.